(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
Offenses in the economic sphere, as a rule, are committed through the use of various business transactions, the study of which requires the use of a complex of knowledge from various economic sciences. Faced with the need to investigate any business transactions or economic indicators, the investigator and the court often resort to the help of expert accountants, who, being universal specialists, can answer questions using a complex of various types of economic knowledge. In this regard, the role of economic specialists, including accounting specialists, will increase. The article discusses the legal basis for the appointment and conduct of forensic accounting expertise. The importance of forensic accounting expertise, the formation of general knowledge in the field of economics and understanding of the industry